Bone Cutter Circumcision in Neonates - Kamil, Mohammed (AL-Kindy College Medical Journal, 2012)
Background: Bone cutter is widely used in theMiddle east area to cut the prepuce during circumcision.Results :One hundred twenty one male neonateswere included in this study.The mean operativetime (MOT) was 6 minutes, mean time ofhealing (MTH) was 5 days, 7 cases (5.9%)developed early & late complications, 2 (1.7%)had bleeding, 3 (2.5%) developed infection, 2(1.7%) developed late complications in the formof meatal stenosis.Settings:Al-Yarmouk Teaching Hospital and aprivate surgical clinic.Aim of the study: To assess the safety ofcircumcision using bone cutter.Methods: Over 6 years period from Jan. 2000till Dec. 2005, one hundred twenty one maleneonates were circumcised under generalanesthesia (GA) using bone cutter.Conclusions: Bone cutter circumcision isfeasible with a relatively lower complicationrate and Shorter MTH and MOT.